Retail Accounting/Retail Merchandise Control (Book). - Schmalz, Carl N. (The Accounting Review, 1935)
Reviews the books "Retail Accounting," by Cecil K. Lyans and Norris A. Brisco and "Retail Merchandise Control," by John W. Wingate.